Balancing family and work: transition to self-employment among new mothers. (5th December 2018) - Jeon, Sung-Hee; Ostrovsky, Yuri
Abstract: We examine the role of self-employment in helping women improve family–work balance. We focus specifically on women who become new mothers and various aspects of their transitions from wage employment to self-employment. Becoming a new mother increases the probability of making such transitions, and our sensitivity analysis addressing selection on the unobservables suggests that this relationship is likely causal. Consistent with the view that such transitions are motivated by the demand for greater working hours flexibility—the weekly working hours of the new mothers making a transition to self-employment become more uniformly distributed than when they were wage earners.